Structure and properties of multilayer plasma Ti-Cu coatings - S.A. Guchenko; N.N. Koval; V.M. Yurov; O.V. Krysina; V.Ch. Laurinas; O.N. Zavatskaya (Қарағанды университетінің хабаршысы. Физика сериясы)
In the article we used the cathodes Ti and Cu. The coatings were deposited on the steel samples by the ionplasma method on the HNB-6.6I1 vacuum unit while simultaneously spraying the above cathodes. Multilayer coatings were created as follows: Ti was applied within 2 minutes, then Ti + Cu were applied within 2 minutes. Totally, 100 layers were applied in an atmosphere of argon and nitrogen. The Ti-Cu-N coatings synthesized by us possessed hardness with an average value of up to 32 GPa, an elastic modulus of 400– 550 GPa, a degree of elastic recovery of 0.69, and a plasticity index of about 0.15, which in terms of parameters is one of the best examples among the well-known hardening coatings. The results of the tribological studies showed that the Ti-Cu-N coating deposited on the optimum mode of vacuum-arc evaporation of a composite Ti-Cu cathode with plasma assisting on a solid substrate has a low friction coefficient, the average value of which is μ = 0.31. The results of X-ray fluorescence analysis confirm the presence of copper in the test coating. Therefore, it can be assumed that copper, without forming its own crystalline phase and not being in the crystal lattice of other phases, is located on the crystallite boundaries in the amorphous state. The time it takes for the copper atoms to form a closed shell around the growing TiN crystallite determines the growth time of the crystallite and, accordingly, its size. The results of studies of structural-phase, tribological and physicomechanical characteristics at high temperatures confirmed that multi-layer Ti-Cu-N nitride coatings can be used as wear-resistant to protect products made of hard metal in the temperature range of 25–700 °С. At temperatures above 700 °С, the structure and properties of the protective layer undergo changes, the coating degrades and does not perform protective functions.